Analysis of Influencing Factors of Sense of Coherence in Patients with Parkinson’s Disease Based on Positive Psychology - Liu, Yang (International Journal of Public Health and Medical Research, 2026)
Parkinson’s disease (PD) is a neurodegenerative disease that seriously threatens human health in contemporary society [1]. Sense of Coherence (SOC) is a concept in positive psychology. By reviewing the SOC of PD patients, this paper elaborates on the current status of SOC in PD patients based on positive psychology theory, explores the influencing factors of SOC in PD patients, and clarifies the important significance of improving the SOC level of PD patients. The study aims to enhance the SOC level of PD patients, improve their quality of life, and provide a theoretical basis for effective clinical interventions.